2015
DOI: 10.1097/md.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute and Early HIV Infection Among Men Who Have Sex With Men (MSM) in San Diego, 2008 to 2014

Abstract: The objectives of this study were to identify risk factors associated with acute and early HIV infection (AEH) among men who have sex with men (MSM) undergoing community HIV testing and to compare demographics in those diagnosed with AEH with those diagnosed at chronic stage of HIV infection.In this retrospective cohort study, we analyzed risk factors associated with AEH among 8925 unique MSM (including 200 with AEH [2.2%] and 219 [2.5%] with newly diagnosed chronic HIV infection) undergoing community-based, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…The “Early Test” is a community-based, confidential AEH screening program that provides point of care rapid HIV serologic testing followed by routine reflex to HIV NAT in all antibody (Ab) negative persons 22, 23 . The UCSD Human Research Protections Program approved the study protocol, consent and all study related procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The “Early Test” is a community-based, confidential AEH screening program that provides point of care rapid HIV serologic testing followed by routine reflex to HIV NAT in all antibody (Ab) negative persons 22, 23 . The UCSD Human Research Protections Program approved the study protocol, consent and all study related procedures.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, this study characterized the temporal relationship between methamphetamine use and sexual risk behavior among HIV uninfected MSM undergoing community-based screening for acute and early HIV infection (AEH) in San Diego, California 22, 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Participants were MSM who reported sexual contact with men during the 12 months prior to testing. Basic demographics, risk behaviors, and frequency of repeat HIV testing from this cohort have been published previously [20][21][22]. An estimated date of infection was calculated for all recently infected persons using previously published criteria for serologic and virologic test results [23].…”
Section: Methodsmentioning
confidence: 99%
“…Syphilis was an independent predictor of HIV acquisition (HR 4.67) in a cohort in San Diego, USA, although a subanalysis of risk factors for HIV in those infected with syphilis was not performed 9. Syphilis also emerged as an independent risk factor for HIV acquisition, although to a lesser extent, in similar studies of larger populations: Pathela et al 10 found a 5.6/100 PYFU incidence of HIV in MSM in New York City, USA, while in iPrEX, Solomon et al 8 found a 7.3/100 PYFU incidence.…”
Section: Discussionmentioning
confidence: 99%